Platform Kesehatan Kucing Dan Konsultasi Dokter Hewan - Fatmasari; Firdha Aprilyani; Romansyah, Ricky (Primakara University, 2024)
Abstract Cats are one of the most popular pets in Indonesia. However, it is important for cat owners to monitor their cats’ health because there is a possibility that they may suffer from infectious diseases. According to the National Center for Biotechnology Information, a study of 883 cats during 2010-2015 revealed that they were infected with several worrying diseases. Unfortunately, the uneven distribution of veterinarians throughout Indonesia is a challenge for cat owners. It is easier to find a veterinarian in urban areas, and other studies also show that cat owners are not always able to take their pets to the clinic due to busy schedules. As a result, many cat owners choose to self-treat their pets for minor illnesses, only visiting a clinic if the condition is severe.